2020
DOI: 10.1177/0731684420918937
|View full text |Cite
|
Sign up to set email alerts
|

Influence of coupling agent on altering the reinforcing efficiency of natural fibre-incorporated polymers – A review

Abstract: Natural fibre-reinforced polymer composites are increasingly replacing commercial composite materials. The limitations of conventional composites materials are overcome by green composites, which are easily available, more eco-friendly and less toxic. In the current scenario, green composites are emerging in the field of material science that involves improving their physical, mechanical and thermal properties. The poor interfacial adhesion and surface incompatibility between natural fibre and biodegradable po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 164 publications
(233 reference statements)
0
25
0
Order By: Relevance
“…Generally, the incompatibility between NF and polymer matrix results in low mechanical strengths of the composites when a compatibilizer is not used. [ 36 ] In addition, [ 37 ] stated that the coupling agent type, its grafting methodology with the matrix and usage ratio played an important role in performance of surface compatibility between the fiber and the polymer matrix. In this case, the enhancement in FS revealed that AKD contributed the compatibility between PLA and wood fiber.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the incompatibility between NF and polymer matrix results in low mechanical strengths of the composites when a compatibilizer is not used. [ 36 ] In addition, [ 37 ] stated that the coupling agent type, its grafting methodology with the matrix and usage ratio played an important role in performance of surface compatibility between the fiber and the polymer matrix. In this case, the enhancement in FS revealed that AKD contributed the compatibility between PLA and wood fiber.…”
Section: Resultsmentioning
confidence: 99%
“…Several works have focused on the enhancement of filler/polymer adhesion by modifying molecules through chemical or physical techniques 145–147 . Mechanical interlocking can be established through proper filler surface modification.…”
Section: Framework Of High‐performance Eco‐composites Productionmentioning
confidence: 99%
“…The increase in impact strength is taken as an indication that the addition of PEg-MA promoted the interaction between the present phases, as seen in the torque rheometry and SEM. As a consequence, it strengthened the system interface, which is essential for the tension transfer between the phases [49,50].…”
Section: Impact Strengthmentioning
confidence: 99%